Customer satisfaction: a study on the efficiency of credit department in Courts Mammoth Berhad Kota Kinabalu / Robiah Ahmad Hijazi - Ahmad Hijazi, Robiah (2006)
This is a descriptive study based on the survey of the customer's perception towards the quality of service in Credit Department, Courts Mammoth Berhad, Kota Kinabalu. Its main objective is to evaluate the level of satisfaction and the weakness in related to SERVQUAL Concept. Statistical Package of Social Science (SPSS) software was used to produce intended results and findings of the study. A sample size of 200 respondents chosen via non-random sampling was fundamental in generating the required inputs. The findings in this study have answered all the research questions set by the researcher. The Credit Employees in CMB have not reached the excellent level of quality service as customers perceived the service rendered by them as only average. Based on the SERVQUAL Concept dimensions, the researcher has identified skills or competencies that is still lack and need to be improved by CMB employees. Finally, 5 (five) recommendations , which are by no means conclusive nor binding, are forwarded, mainly for academic purpose as well as for future study and evaluation.